Sistem Monitoring dan Kontrol Laju Infus Berbasis Internet of Things Menggunakan Sensor Berat dan Optocoupler - Abdul Floranda; Sulthon Mohd Fitrah; Fathurrahman (Universitas Muhammadiyah Surabaya, 2026)
Intravenous (IV) fluid monitoring in hospitals is commonly performed manually, which may cause delays in fluid replacement and inaccurate drip rate adjustments. This study aims to design and implement an Internet of Things (IoT)-based system for monitoring and controlling the IV drip rate in real time. The system uses a load cell sensor with an HX711 module to measure fluid volume, an optocoupler to detect the drip rate, and an ESP32 microcontroller as the main controller. A closed-loop control method is applied using a stepper motor to adjust the infusion tube opening and maintain the drip rate at a setpoint of 170 drops per minute. Measurement data are displayed on an LCD and transmitted to a smartphone application via WiFi for remote monitoring. Experimental results show that the system achieves an average volume measurement error of 3.41% and a drip rate control error of 0.94%. The system also provides an early warning through a buzzer when the fluid volume approaches the minimum threshold. These results indicate that the proposed system can perform IV monitoring and control accurately and reliably while supporting remote monitoring through IoT technology.